Basketball shooting motion analysis according to the BEEF concept - Ahmad Panji Ramadhan; Fajar Awang Irawan (Sriwijaya Journal of Sport, 2022)
This research aims to find out and analyze shooting movement skills in accordance with the concept of BEEF (balance, eyes, elbow, follow-through) in sports or basketball games that are reviewed in terms of biomechanics. BEEF is a shooting concept that makes it easier for athletes to understand and handle shots properly and correctly with the advantage of being more efficient and effective in the shooting. The methods in this study use quantitative descriptive by using survey methods with test and measurement techniques to collect data. Sampling techniques in this study use purposive sampling because it has certain criteria in determining samples. A total sample of 8 male athletes of Depok City Elite Skills Club had approved this research procedure by signing informed consent. The results showed that basketball shooting speed has an average of 1.94 ± 0.56 m/s and an average time of 1.30 ± 0.18 seconds. This research confirms that basketball shooting movements in accordance with the BEEF concept fall into the category of Inappropriate and the results of the level of conformity with the average fall into the corresponding category. The limitations of this study only show kinematic data including distance, times, speed, and angle. In the next researcher is expected to be able to measure kinetic data to find out what is the strength and darkness of athletes when shooting.